Technological benefits of relocation and extension a continuous part of the coal transport system - Doderović Aleksandar; Gomilanović Miljan; Stanić Nikola; Stepanović Saša; Kržanović Daniel (Mining and Metallurgy Engineering Bor)
Due to the changing conditions of the working environment or its insufficient knowledge, the coal exploitation takes place with smaller or larger deviations from the designed or planned activities. Depending on which segment of the entire exploitation system the deviation occurred, it will also depend on the extent to which the deviation will affect the profitability and efficiency of exploitation. If major accidents are excluded, the technological process of transport has the greatest impact on the efficiency and economy of exploitation. The newly created situation at the open pit Gacko - Central Field in terms of coal transportation was analyzed in the presented paper. Also, the benefits are presented that arise as a result of reconstruction the combined coal transport system, continuous and discontinuous part. The system reconstruction included the extension of continuous part of transport and relocation the crusher closer to the front of the works, in order to reduce operating costs. On the other hand, discontinuous transport is reduced to the zone where the works are carried out, in order to reduce the operating costs and use the maneuverability of discontinuous equipment. This paper explains the technological-organizational, economic and ecological benefits of reconstruction the coal transport system, for the short and long term.